Steel stocks and flows of global merchant fleets as material base of international trade from 1980 to 2050. (March 2022) - Kong, Xianghui; Feng, Kuishuang; Wang, Peng; Wan, Zheng; Lin, Lin; Zhang, Ning; Li, Jiashuo
Graphical abstract: Highlights: A dynamic MFA model is used for quantifying global ship steel stocks and flows. A global ship steel in-use stocks database is built from 1980 to 2019. Ship steel use and waste dramatically increased in last four decades. Trajectories of ship steel use and waste generation by 2050 are estimated. Abstract: Exploring the dynamic changes of steel from the ships is critical for developing sustainable strategies for waste management of shipping industry. However, the information of stocks and flows of ships and related steel is currently unavailable, hindering the sustainable development of shipping industry. By collecting dispersed information on production, use, material composition, and end-of-life management of five types ships, we first estimated the historical steel stocks and flows respect to global ships from 1980 to 2019, and further projected the amount of steel scraps from shipbreaking by 2050. The steel stocks of ships increased by 2.6 times from 208.4 Mt in 1980 to 542.9 Mt in 2019. The top 2 regional contributors, Asia and Latin America & the Caribbean, were together responsible for about half of the total increase. A transition from oil tankers to container ships and bulk carriers reduced the in-use steel stock due to the lower steel intensity of the latter. The rapid increase of ship stocks after year 1980 led to significant increase of steel scrap in the 2010 s, reaching 10.1 Mt/year in 2019. Our projections showed that the steel from scrapped ships worldwide will increase by around 4-fold to 40.4–47.3 Mt/year by 2050, which imposed a great challenge on coordination of recycling ship-related steel and require long-term planning on ship recycling facility development. By identifying the stocks and flows of ships and related steel, this study provides insights for the steel waste and recycling management of end-of-life ships worldwide.